Parents, learning and project Head Start: A socio-political analysis - Peggy A. Sissel (Adult Education Research Conference, 1994)
This ethnographic study of parent involvement and education in Head Start addressed adult learning within the context of an interactive social system. This holistic approach based on both staff and parent perspectives revealed that teaching and learning were affected by issues of Capacity, uses of Power and the development of Connections among staff and parents.